Bimbingan Mengelola Keuangan dan Strategi Pemasaran UMKM di Kota Ternate - Rizki Wahyu Utami Ohorella; Sheila Kusumaningrum; Mahardika Catur Putriwana Malik; Suwito Suwito (Lembaga Pengembangan Kinerja Dosen, 2024)
Lack of capital and knowledge of technological development to raise capital, the purpose of this service activity is to provide guidance to MSME actors in Ternate city, the method used is FDG, and at the same time direct guidance to fostered MSME actors. The activity participants who attended were 30 people at the implementation of the service. good financial management and effective marketing strategies, MSEs in Ternate City can improve their business performance and contribute more to the national economy. Therefore, continuous training and mentorship are needed to support the growth and sustainability of the MSMEs in Ternate City.